STUDI KUALITATIF: KOMITMEN MANAJEMEN TERHADAP TINGKAT RISIKO KEBAKARAN DI HOTEL X KOTA SEMARANG - Gasita Putri Sari Utami; Daru Lestantyo; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Hotel X is a three-star hotel that has 4 floors with a fire risk. There are incompleteness of fire protection facilities and infrastructure in the hotel, such as the absence of fire alarms, directions on the exit facilities, and the absence of safety signs on the emergency stairs. The purpose of this research was to analyze the management's commitment towards the level of fire risk in Hotel X Kota Semarang. This research is a qualitative descriptive study by conducting in-depth interviews with seven main informants and three triangulation informants. The results of this study indicate that there is a fire fighting management that includes a fire prevention team, fire fighting procedures, fire fighting facilities and infrastructures, and the provision of human resources. The fire fighting organization at hotel X consists of all employees who work in shifts and play a role in combating fires. Fire fighting procedures have been established and must be followed by all employees in order to create good supervision using logical sequences and carried out repeatedly. Infrastructure and facilities for handling fires in hotel X including active and passive protection facilities such as the availability of fire extinguishers, fire hydrants, and evacuation assembly point. Human resources in hotel X are qualified to cope with emergencies because they have been given periodic training to prevent, reduce and extinguish fires. The researcher recommends to install fire alarms throughout the hotel, provide warning signs on exits or evacuation routes, provide safety signs on emergency stairs, and provides special identification to the fire fighting team to find out the identity and authority of the fire fighting team.